2003
DOI: 10.4049/jimmunol.171.6.3010
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Function of Reactive Oxygen Species in Dendritic Cells During Antigen Presentation

Abstract: Although reactive oxygen species (ROS) have long been considered to play pathogenic roles in various disorders, this classic view is now being challenged by the recent discovery of their physiological roles in cellular signaling. To determine the immunological consequence of pharmacological disruption of endogenous redox regulation, we used a selenium-containing antioxidant compound ebselen known to modulate both thioredoxin and glutaredoxin pathways. Ebselen at 5–20 μM inhibited Con A-induced proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
162
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(175 citation statements)
references
References 61 publications
12
162
0
1
Order By: Relevance
“…It was also demonstrated that the redox imbalance induced by skin sensitizers is important in the regulation of DC functions [5,38,39,41,47,61]. Therefore, the increase in Trx-1 mRNA expression observed in .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was also demonstrated that the redox imbalance induced by skin sensitizers is important in the regulation of DC functions [5,38,39,41,47,61]. Therefore, the increase in Trx-1 mRNA expression observed in .…”
Section: Discussionmentioning
confidence: 98%
“…LPS is recognised by a LPS-activation cluster [56] that could activate two diVerent pathways. Upon stimulation with LPS, ROS production occurs [39,62], which appears to break the inactive complex reduced Trx-1/ASK1, thus allowing the subsequent recruitment of TRAF6 to the ASK1 signalosome [21,54]. The activated ASK1 signalosome induces Nrf2/ ARE-mediated expression [66], which is involved in Trx-1 protein expression [29,67].…”
Section: Discussionmentioning
confidence: 99%
“…In DC, oxygen radicals were implicated in both DC differentiation (43) and maturation (26,27) and in IL-8/CXCL8 production (24,25). Controversial data are present in the literature about the inhibitory action (52) or the positive role (26,53) of oxygen radicals on the ability of DC to stimulate T cell response. To evaluate the contribution of NADPH oxidase-dependent oxygen radicals on DC functions, we generated DC from monocytes obtained from CGD patients.…”
Section: Discussionmentioning
confidence: 99%
“…ROS response has been reported not only in phagocytes but also in antigen-presenting cells (APCs), such as dendritic cells (DCs) [30]. Also, T cells have been reported to express Ncf1 during antigen presentation and activation [31], adding further complexity to the process of finding the mechanisms behind the phenotype.…”
Section: Pathway Analysismentioning
confidence: 99%
“…There are a number of pathways that are proposed to be affected by free radicals and state of oxidation. On the antigenpresenting level, it has been shown that by inhibiting ROS production, the proliferation of T cells in response to antigen presentation of DCs is prevented [30], suggesting that the burst response in an APC could modulate the antigen presentation capacity of that cell.…”
Section: Pathway Analysismentioning
confidence: 99%